Analysis Quality of Service (QoS) on Ad Hoc Networks with Network Simulator Version 3 (NS-3) - Rahmadani Rahmadani; Supiyandi Supiyandi; Manalu Lia Kristina (Geviva Publisher, 2023)
QoS (Quality of Service) results for throughput, packet loss and delay as well as data transfer process performance tests were carried out with the NS-3 simulator based on the number of nodes that are continuously added according to the scenario on the ad hoc network. The scenario of adding nodes is carried out in stages starting from 10 nodes, increasing to 20 nodes, up to 40 nodes. The results of the analysis and measurements obtained for throughput produce an average value of 3.1872 Kbps so that it is included in the good category. The packet loss parameter produces an average value of 3.48% which is included in the good category and the delay parameter produces an average value of 6,824 ms which is also included in the good category. The final results of the ad hoc network simulation process with NS-3 are presented in graphical view